Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1001/jamanetworkopen.2022.34880
|View full text |Cite
|
Sign up to set email alerts
|

Patient Use of Physicians’ First (Given) Name in Direct Patient Electronic Messaging

Abstract: This cohort study examines factors that may contribute to whether patients address physicians differently through electronic messaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…As the thousand cuts mount, with experiences of bias at work, surging EHR workload (that is variably and often not compensated), disproportionate domestic and childcare responsibilities, and the collision of personal and professional responsibilities that often remove women physicians completely from the medical workforce, is it any wonder that the Great Resignation movement impacts women in medicine most drastically? In our view, the work by Harvey and colleagues and those before them supports urgent action by engaged and diverse leadership to reduce and mitigate the impact of unconscious bias to reduce burnout and attrition.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…As the thousand cuts mount, with experiences of bias at work, surging EHR workload (that is variably and often not compensated), disproportionate domestic and childcare responsibilities, and the collision of personal and professional responsibilities that often remove women physicians completely from the medical workforce, is it any wonder that the Great Resignation movement impacts women in medicine most drastically? In our view, the work by Harvey and colleagues and those before them supports urgent action by engaged and diverse leadership to reduce and mitigate the impact of unconscious bias to reduce burnout and attrition.…”
mentioning
confidence: 90%
“…In this issue of JAMA Network Open, Harvey and colleagues 1 analyzed more than 90 000 electronic messages sent to physicians by more than 34 000 patients and found that women physicians, doctor of osteopathic medicine (DO) physicians, and primary care physicians (PCPs) were more frequently addressed by first name instead of formal professional title. The authors found that women had greater than twice the odds as men to be addressed by their first name, even after adjusting for patient gender, physician age, degree, trainee vs faculty member, and specialty.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Female physicians also further experience inequities at work, including a higher burden of after-hours documentation and over 25% more patient messages compared to men [13,14]. Surveys demonstrate that female physicians are more likely to turn down academic opportunities and leadership positions and are not comfortable discussing work-life integration with department leadership [15].…”
Section: Rationale For Novel Parental Wellness Program (Pwp)mentioning
confidence: 99%
“…In a previous survey of 333 physicians, almost three-quarters of respondents reported being called by their first (given) name, with annoyance reported in 61%. 1 A recent study revealed that having "DOCTOR" identification badge labels were associated with female physicians and physicians underrepresented in medicine experiencing substantially fewer episodes of bias from misidentification. 2 Here, we aim to determine factors that are associated with whether patients addressed physicians differently through electronic messaging.…”
Section: Introductionmentioning
confidence: 99%